2008 IEEE International Symposium on Consumer Electronics 2008
DOI: 10.1109/isce.2008.4559428
|View full text |Cite
|
Sign up to set email alerts
|

Light-weighted Internet protocol version 6 for low-power wireless personal area networks

Abstract: This paper proposes an architectural design of light-weight IPv6 (LWIPv6) for low-power wireless personal area networks (LoWPANs). The LoWPAN is a simple and lowcost wireless communication system, which allows wireless connectivity in a variety of applications with requirements of limited power and relaxed throughput. LoWPAN devices conform to the IEEE 802.15.4 standard specified by the IEEE Computer Society. This paper also suggests how to make IP and IPv6 networking benefits in LoWPANs. Consequently, this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The survey had shown that, there is a lots of scope for improvement in the area of signalling in IR. One of the ways for the future is superseding the existing trackside components with wireless sensor nodes, with the implementation of Time Slotted Channel Hoping (TSCH) following IEEE 802.15.4 for 6LoWPAN [26] networks we can achieve deterministic data transfer with high reliability with cheaper equipment when compared with the current scenario. From the resent trends it is given that the IR revenue has obtained a growth of 22,854.67 crores in the financial year of 2018-19.…”
Section: Figure 10 Communication Based Train Controlmentioning
confidence: 99%
“…The survey had shown that, there is a lots of scope for improvement in the area of signalling in IR. One of the ways for the future is superseding the existing trackside components with wireless sensor nodes, with the implementation of Time Slotted Channel Hoping (TSCH) following IEEE 802.15.4 for 6LoWPAN [26] networks we can achieve deterministic data transfer with high reliability with cheaper equipment when compared with the current scenario. From the resent trends it is given that the IR revenue has obtained a growth of 22,854.67 crores in the financial year of 2018-19.…”
Section: Figure 10 Communication Based Train Controlmentioning
confidence: 99%